Answer:
![\begin{gathered} x=(15)/(p) \\ x=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/1hygluf6s5isulyqfwchye2c71x9qwh9i5.png)
Explanation:
To solve the equation use inverse operations. Addition and subtraction are inverse operations, multiplication, and division too.
Therefore, solve for x in the expression below:
![\begin{gathered} 4(px+1)=64 \\ px+1=(64)/(4) \\ px+1=16 \\ px=16-1 \\ px=15 \\ x=(15)/(p) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/qzijbjf4dpu59t74x0j73n7gt63rpa95nl.png)
Now, substitute p=-5 into the equation we got above:
![\begin{gathered} x=(15)/(-5) \\ x=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/8taf9bsf37ov1ct7b3bhfeoaw4dz40r6w2.png)